Pembentukan Karakter Pada Anak Usia Dini Di Taman Kanak-Kanak Aisyiyah Mamajang Kota Makassar - Nuraini Nuraini (Al-Riwayah : Jurnal Kependidikan, 2020)
This study aims to determine first, the process of character building in early childhood at Aisyiyah Mamajang Kindergarten, Makassar City, second, to determine whether there are supporting factors and inhibiting factors for the success of the character building process in Aisyiyah Mamajang Kindergarten, Makassar City and third, to determine the results of the formation process. characters at Aisyiyah Mamajang Kindergarten, Makassar City. This research is a qualitative research using a multidisciplinary approach with multiple perspectives including: philosophical, pedagogical, psychological and theological approaches. Sources of data in this study were the principal, administrative staff, teaching staff, and parents of students, the Head of the PAUD Division of the Education and Culture Office and the Head of the PAI Section in PAUD / Kindergarten in the Regional Office of the Ministry of Religion, South Sulawesi Province. The results showed that the character building of early childhood at TK Aisyiyah Mamajang Makassar ran optimally where the behavior or character of most of the students experienced significant changes after receiving character education through the BCCT (Beyond Centers and Circle Tiimes) method and programmed activities and familiarization activities ( exemplary), by actualizing character values; religious, honest, patriotism, discipline, communicative, responsibility ,. So that the change from the character of a spoiled child to being independent, a cowardly one to being brave, one who is quiet and closes oneself becomes easy to socialize / communicate, more religious, memorizes short chapters, memorizes prayers and performs dhuha prayers regularly, although there are still some students who have not been able to or experience slow changes due to various factors. Early childhood is a period of forming a child's personality or character. When a child's character is formed from an early age, in the future the child will become an individual with character as well. The results of this study suggest that Aisyiyah Mamajang Kindergarten can be a role mode for Aisyiyah Kindergarten in particular and other Kindergartens in general.